2012
DOI: 10.1073/pnas.1121423109
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-derived nanoparticles for immunostimulatory RNA adjuvant delivery

Abstract: The specific activation of Toll-like receptors (TLRs) has potential utility for a variety of therapeutic indications including antiviral immunotherapy and as vaccine adjuvants. TLR7 and TLR 8 may be activated by their native ligands, single-stranded RNA, or by small molecules of the imidazoquinoline family. However the use of TLR7/8 agonists for in vivo therapy is limited by instability, in the case of RNA, or systemic biodistribution and toxicity in the case of small molecule agonists. We hypothesized that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 57 publications
0
61
0
Order By: Relevance
“…Lipidoid is a lipid-like material consisting of an amine-containing head group and hydrocarbon tails, which is synthesized via epoxide ring-opening by amine substrate [77]. Study on cynomolgus monkeys showed that iv.…”
Section: Lipidoid Nanoparticlesmentioning
confidence: 99%
“…Lipidoid is a lipid-like material consisting of an amine-containing head group and hydrocarbon tails, which is synthesized via epoxide ring-opening by amine substrate [77]. Study on cynomolgus monkeys showed that iv.…”
Section: Lipidoid Nanoparticlesmentioning
confidence: 99%
“…Efforts have primarily focused on constructs for immunostimulation (IS) and include complexing oligonucleotides with albumin (15), gold nanoparticles with two-component external coronas consisting of IS-oligonucleotides together with protein antigens (16), gold nanoparticle-IS-oligonucleotide conjugates (17), IS-oligonucleotides conjugated to polymeric nanoparticles (18), and IS-oligonucleotides in complex with lipids (19). Although these studies have uncovered the promise of nanomaterials for immunomodulation, it is still unclear what the dominant structural factors are.…”
mentioning
confidence: 99%
“…Unmodified naked siRNAs are degraded rapidly by nuclease in the circulation and removed efficiently through renal clearance (34,35). In addition, activation of nonspecific innate immune stimulation of short RNA sequences could be a significant problem with repetitive and high-dose therapeutic application of siRNAs (5,6). Therefore, to achieve optimal in vivo siRNA delivery and specific silencing, it is imperative to develop modified siRNA or strategies that allow protection of siRNAs from nuclease degradation and facilitate cellular uptake for efficient gene silencing without significant immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Naked nucleic acid molecules, including synthetic siRNA, are degraded easily by ubiquitous nucleases either in the circulation or inside cells, and they are unable to enter cells through passive diffusion mechanisms because of the large molecular weight and polycationic nature of the chemical structure (4). In addition, the nonspecific innate immune-stimulatory function of siRNA could be a serious problem, especially for repetitive and high-dose therapeutic applications (5,6). In the last decade, various approaches have been developed to overcome these issues.…”
mentioning
confidence: 99%